RESEARCHING SCIENTIFIC SOURCES ON OTITIS MEDIA (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Before the modern era of antibiotics, otitis media was very often accompanied by deleterious consequences, as the following quote from Hippocrates shows: ‘Acute earache with prolonged fever is to be feared, for there is a danger that a person may fall into delirium, followed by death’. Surgical treatment of chronic otitis media probably dates back to antiquity, as drainage of abscesses by military surgeons and other specialists, was common. However, little evidence of this has survived. The history of chronic ear disease is well covered in the works of Milstein and Briggs